2018
DOI: 10.1177/1059840517752456
|View full text |Cite
|
Sign up to set email alerts
|

Public School Nursing Practice in the United States

Abstract: School nursing practice has changed dramatically over the past 20 years, yet few nationally representative investigations describing the school nursing workforce have been conducted. The National School Nurse Workforce Study describes the demographic and school nursing practice patterns among self-reported public school nurses and the number and full-time equivalent (FTE) positions of all school nurses in the United States. Using a random sample stratified by public/private, region, school level, and urban/rur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
199
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(207 citation statements)
references
References 14 publications
5
199
0
3
Order By: Relevance
“…School nurses provide basic health care to children around the country, administering medications, conducting screening and education, addressing acute conditions, and helping to manage chronic ailments such as asthma and diabetes. Coverage varies, however, with a 2018 survey indicating that nearly 20 percent of schools lack nursing support and about 40 percent of nurses serve three or more buildings, findings which were more prevalent in rural than urban school districts (Willgerodt, Brock, & Maughan, 2018). In addition, there are 2,584 school-based health clinics, which in 2016-17, served 10,629 schools and over 6.3 million students in 48 states; Washington, DC; and Puerto Rico-more than twice the number of centers in 1998 (1,135; Love, Schlitt, Soleimanpour, Panchal, & Behr, 2019).…”
Section: The Role Of Schools In Children's Well-beingmentioning
confidence: 99%
“…School nurses provide basic health care to children around the country, administering medications, conducting screening and education, addressing acute conditions, and helping to manage chronic ailments such as asthma and diabetes. Coverage varies, however, with a 2018 survey indicating that nearly 20 percent of schools lack nursing support and about 40 percent of nurses serve three or more buildings, findings which were more prevalent in rural than urban school districts (Willgerodt, Brock, & Maughan, 2018). In addition, there are 2,584 school-based health clinics, which in 2016-17, served 10,629 schools and over 6.3 million students in 48 states; Washington, DC; and Puerto Rico-more than twice the number of centers in 1998 (1,135; Love, Schlitt, Soleimanpour, Panchal, & Behr, 2019).…”
Section: The Role Of Schools In Children's Well-beingmentioning
confidence: 99%
“…101,102 One literature review revealed that school nurses can improve attendance among students with chronic absenteeism and that lower nurse-to-student ratios were associated with improved school-level attendance rates. 103 Many schools have nurse coverage only part-time, and some schools do not have nurse coverage at all 104 ; therefore, a health aide or other school personnel may provide some school health services. The services provided by health aides or other school personnel are essential when a nurse is not available, but these other providers typically do not have nursing training.…”
Section: School Nursesmentioning
confidence: 99%
“…A key attribute of school nursing is advocacy: for student health, safe environments, accessible health services, educational funding, and assuring that all policies supporting healthy students in healthy environments are in place (Mazyck, Cellucci, & Largent, 2015;NASN, 2017b). School nurses, grounded in ethical and evidence-based practice, are leaders who bridge health care and education, provide care coordination, advocate for quality student-centered care, and collaborate to design systems that allow individuals and communities to develop their full potential (NASN, 2017b;Willgerodt, Brock, & Maughan, 2018). Not surprisingly, advocacy is also a fundamental characteristic of SLBs, who "use their knowledge, skill, and position to secure for clients the best treatment" (Lipsky, 2010, p. 72).…”
Section: Discussionmentioning
confidence: 99%